The Aging Workforce Management in Business Sectors (Quest Journal of Management and Social Sciences, 2021)
Background: Aging society affects good planning in workforce management for sustainable business running. Workforce management is not only the duty of human resources but also promotes the strategy for effective management.Objectives: The objective of this study is to analyze the aging workforce management in business sectors.Method: The research reviews relevant literature and, based on the evidence of theories about age-diverse management, creates a framework related to antecedent factors and the following factors. The testing applied the CBSEM model with a sample group of 300 respondents.Result: The result found that planning “capacity in the workplace” and “knowledge management” are two factors that affect the potential corporate reputation efficiency of an organization significantly via “cultural value” and “social value” which were completely transformational.Conclusion: The result of the study regarding the theory evidence and support research from overseas has a problem in applying to practice with an empirical result that differs locally. Therefore, the model needs to be verified with the local data, and develop a suitable model.